KEPRIBADIAN DIRI TOKOH ALINA PADA NOVEL HATI SUHITA KARYA KHILMA ANIS ( KAJIAN PSIKOLOGI BEHAVIORISME ) - Siti Nurkhalimah Fatmawati; Susi Darihastining; Akhmad Sauqi Ahya (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Personality includes all thoughts, feelings, behavior, consciousness and unconsciousness. Personality guides people to. adapt to the social and physical environment. Psychology behaviorism is a science that studies human personality by controlling emotions in humans. This control is carried out by controlling oneself towards positive things, or making positive decisions for the future as needed. The novel Hati Suhita is one of Khilma Anis's works in which it describes the journey of the meaning of love along with the attachment of faith, expresses social reality clearly about the relationship between two people, the relationship with parents, and the relationship with God and all are attached to the personality of a character so that they still maintain so that love does not turn into a mistake. In this regard, this study will discuss how the main character's stimulus in the novel Hati Suhita by Khilma Anis. Stimulus is a stimulus from outside the individual that is happening to humans and forming a behavior in humans. Stimulus occurs because of several variables that exist in the surrounding environment. The data in this study are a series of paragraphs, sentences, monologues, and dialogues in the novel. Data collection techniques in this study used library research techniques and data analysis techniques in this study used descriptive analytic techniques.